Bethanie Pack: capstone - Pack, Bethanie, artist (Colorado State University. Libraries, 2014)
The artist's statement: This body of work investigates my own identity and the identities of strangers. My sense of self is profoundly impacted by the relationships in my life, in both a positive and negative light. For example, my identity in relation to my mother is fraught with sentimentality, love, and the constant quest for approval. In relation to my boyfriend, it is overwhelmed with a sense of piety, lament, and a desire to rescue him, even when that compassion becomes self-destructive. In order to address the sentimental and nurturing aspects that are imprinted within me, I created paintings using family photos, floral fabrics, and lace that are indicative of the domestic. Additionally, these paintings are comfortably scaled to evoke a sense of the familial. Moving beyond myself as the subject, I then created postcards which allowed complete strangers to anonymously respond to a specific prompt about their identity. The responses were mailed back to me. The prompts included: describe a moment when you felt the most emotion, and describe a defining moment of your life. Interestingly, all the responses I received revolved around a relationship with another person, even though the prompts asked the participant to focus on themselves. Along with traditional painting, I utilized sanding techniques, collage, and line drawing. In the paintings about strangers, I also incorporated their handwriting from the responses. My slow process of building up each layer, and then sometimes sanding it away, creates a very unsettling space to dissect and digest the various aspects of either mine of someone else's sense of self. It is the moments between the layers, and the physical act of sanding away that truly speaks to the anxiety I feel for capturing and addressing the complexity of identity. Each layer fights with the others for a defining moment. Some contain an apparent tentativeness. These combatting layers embody the psychologically progressive and destructive layers that construct a sense of identity. Through this process, I find that identity is convoluted and complex, shifting through time and place, and fluctuating based on relationships. The importance of relationship reflective within the abstract pieces embodies a feeling, a moment, an emotion. They provide a platform for the viewer to experience empathy for another, what I believe to be the height of human experience and relational identity. Through the process of defining my identity, as well as learning about how strangers briefly define their own identities, I have come to the conclusion that identity is not autonomous or self-sufficient, but rather contingent upon our interactions and relations with others.
Relational identity
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.